The Philosophical Confrontation of Mulla Sadra with Bin Arabi’s Mysticism - Abdullah Salavati (حکمت اسرا)
Indeed Mulla Sadra had been extensively influenced by bin Arabi’s school of thought. This is why some have considered Mulla Sadra, not as the founder of a school of thought, but as subordinate to Mulla Sadra. However, in this paper first Mulla Sadra’s critical view of bin Arabi’s mysticism and a list of his criticisms in this regard will be presented. Then it will be discussed that, though Mulla Sadra’s school of thought initially accepts bin Arabi’s mystic views, there are some differences between these two as well. These differences can be found in the existential views, diversity of methods, and emphasis that is put on logics. Moreover, since Mulla Sadra’s philosophy is like an epistemic network that includes speculation, problems, method and purpose, if some of its sides are changed other sides will also change dramatically.